The Influence of Financial Performance on Company Value with Good Corporate Governance and Corporate Social Responsibility as A Moderation Variable on Manufacturing Listed on The Indonesia Stock Exchange for The Period 2019-2023 - Wasti Naramarito Pardede; Agung Dharmawan Buchdadi; Etty Gurendrawati (Lafadz Jaya Publisher, 2024)
The purpose of this research is to examine the effect of financial performance on firm value, to test the effect of Good Corporate Governance on firm value, to determine whether Good Corporate Governance can moderate the relationship between financial performance and firm value, to investigate the effect of Corporate Social Responsibility on firm value, and to determine whether Corporate Social Responsibility can moderate the relationship between financial performance and firm value. Financial performance is proxied by ROA and ROE. Firm value is proxied using Tobin's Q. Good Corporate Governance is measured by the proportion of independent commissioners, managerial ownership, and institutional ownership. Meanwhile, Corporate Social Responsibility is measured using the Corporate Social Responsibility Disclosure Index based on the indicators in the GRI G4 Sustainability Reporting Guidelines. The subjects of this study are all manufacturing companies listed on the Indonesia Stock Exchange for the period 2019-2023. The total sample of the study is 39 companies. The results of this study indicate that financial performance significantly affects firm value with a negative regression coefficient (-0.348) and a high t-statistic (-7.547, p < 0.05). Good Corporate Governance (GCG) also significantly influences the relationship between financial performance and firm value, as indicated by a positive regression coefficient (4.297) and a significant t-statistic (3.561, p < 0.05). Corporate Social Responsibility (CSR) also significantly affects the relationship between financial performance and firm value, with a positive regression coefficient (1.470) and a high t-statistic (6.280, p < 0.05).